Diving into Diagnostic Complexity: A Case Study of Spontaneous Hemothorax - Maryam Sarkhosh; Atiyeh Sadat Sajadi; Omid Moradi Moghaddam; Parisa Moradi Majd (Archives of Anesthesia and Critical Care)
Hemothorax, a condition characterized by blood accumulation in the pleural space, primarily results from trauma, affecting around 300,000 individuals annually in the United States. Spontaneous cases, although rare, pose diagnostic challenges due to diverse etiologies such as coagulation disorders, vascular anomalies, and neoplastic diseases. Diagnostic modalities like computed tomography, chest X-ray, and ultrasound play a crucial role in identification. A 29-year-old female with multiple sclerosis presented with severe chest symptoms, leading to pleural effusion requiring chest tube insertion. Despite inconclusive rheumatologic tests, evaluations excluded malignancies and thromboembolic events, enabling transfusions and supportive care. Global cases underscore varied causes of spontaneous hemothorax, with management strategies emphasizing interdisciplinary care. While certain conditions were ruled out, unresolved rheumatologic concerns persisted post-discharge, highlighting the need for further research to enhance diagnosis and management of spontaneous hemothorax.